Regulation of osteogenic differentiation in vascular smooth muscle cells under high-glucose condition - Guo, Jingjing; Du, Laijing (Frontiers in Endocrinology, 2025)
Diabetic patients have a higher tendency for vascular calcification (VC). This indicates a possible link between abnormal glucose metabolism and the development of VC. High glucose levels are a major cause of vascular calcification in diabetic patients. Vascular smooth muscle cells (VSMCs) are important functional units of the arterial media and show heterogeneity. Sustained hyperglycemia drives VSMCs to undergo a phenotypic transition from contractile state to osteo-/chondrogenic lineages through multiple pathophysiological mechanisms. Specifically, hyperglycemia stimulates metabolic reprogramming. This includes enhancing advanced glycation end products (AGEs), activating the diacylglycerol-dependent protein kinase C (PKC) pathway, disrupting the pentose phosphate flux (PPP), and dysregulating the hexosamine biosynthesis pathway (HBP). These changes trigger vesicles-mediated mineralization (including matrix/extracellular vesicles), oxidative stress, inflammatory cascades, and an imbalance between autophagy and apoptosis. This review systematically describes the metabolic remodelling induced by high glucose and its regulatory mechanisms in vascular calcification.